Estudo da influência da deformação por cisalhamento extrusão em canal angular e laminação assimétrica nas propriedades mecânicas do alumínio AA 1050 - Vega, Marcelo Clécio Vargas (2014)
It is known that the formability of aluminum alloy AA1050 is not favored when sheets are produced by conventional rolling due to the appearance of intense cube texture {100} <100> after recrystallization heat treatment. The objective of this study was to investigate whether components of shear processes can improve this property. For this work two processes of plastic deformation introducing shear stresses were selected: Equal channel angular extrusion (ECAE) and asymmetric rolling; these processes were compared to conventional rolling. In conventional rolling deformation results mainly compressive stresses. In the ECAE process shear is induced in the intersection of two channels of the same geometry that intersect by an angle  In the asymmetric rolling the shear stress is basically increased due to the speed variation between the rolls. An AA1050 aluminum sheet produced by the twin roll casting process was used in this study. The deformations were performed basically in 4 paths: i) conventional rolling, 70% reduction, ii) ECAE 1-8 passes, iii) ECAE 1-4 passes followed by conventional rolling with reduction of 70% and iv) Asymetric Rolling with reductions 30-50%. The mechanical and microstructural characterization of the deformed state was performed and the formability after annealing heat treatment was studied. ECAE deformation reduced the grain size, which measured by EBSD and transmission electron microscopy yield 1 micrometer. The evolution of equivalent strain compared with the increase of the hardness indicated a grain size stabilization of the grain/cell after four ECAE extrusion passes. After 8 passes the fraction of high angle boundaries exceeded the low-angle boundaries, ie dynamic recrystallization occurred during deformation. The texture after one pass ECAE approached the ideal texture for a 120 ° ECAE die. For deformations with 4 - 8 ECAE passes, the texture evolved into scattering the orientations having the {111} plane parallel to the surface ( fiber), and into the formation of rotated cube {100} <110> and rotated Goss {110} <110> orientations. The conventional rolling after ECAE returned the orientations to typical rolling textures: brass, copper and Goss. Deformation by asymmetric rolling with a difference of tangential velocity of 1.2 imposed shear stress, but it was necessary to decrease the reduction rate from 10% to 5% per pass in order to appreciably modify the texture. Comparing the formability of the deformed material, it was observed that ECAE increased the penetration depth in the Erichsen test, while rolling decreased the Erichsen index. Asymmetric rolling reduced the intensity of texture and destroyed the symmetry of the crystallographic orientations. The asymmetric rolled sample presented better formability than the rolled samples. After annealing, the samples of conventional rolling, with or without ECAE pre - strain, showed typical textures of annealed laminated material with high cube texture type. The  fiber was not stable in the ECAE annealed samples. Although the overall texture intensity remained low, increasing ECAE deformation before heat treatment strengthened the Goss {110} <001> orientation. For the asymmetric rolling the fiber orientations <100>// ND was scattered and both rotated cube and cube orientations were present. The lowest index of planar anisotropy was obtained in the sample annealed after four ECAE passes, representing a lower tendency to fail, This sample also presented an index of penetration in Erichsen testing of the same order of conventionally rolled sheets. It has been shown that both ECA as the asymmetric rolling deformation can significantly modify the texture of deformation and annealing, and improve the characteristics of formability of aluminum alloy 1050. This processing step should be located at the end of mechanical forming process before final annealing.